2021
DOI: 10.33007/ska.v10i2.2423
|View full text |Cite
|
Sign up to set email alerts
|

Jogo Tonggo : Solidaritas Masyarakat di Era Pandemi Covid-19

Abstract: This paper examined the Jogo Tonggo policy issued by the Central Java Provincial Government in the face of the Covid-19 pandemic. Methodology: This research is a qualitative descriptive, data were collected by in-depth interviews with respondents who were selected by snowball sampling. The research was conducted in Purworejo Regency. Result: The Covid-19 pandemic changed the pattern of relations between communities through the local (village) self-contained quarantine that was enforced in villages. Several vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 2 publications
0
3
0
6
Order By: Relevance
“…Sebagai bangsa yang majemuk, masyarakat Indonesia sudah terbiasa untuk hidup berdampingan dengan segala keragaman budaya yang ada sebagai wadah interaksi sosial dengan menjunjung nilai dan kebersamaan. Kentalnya budaya gotong royong di Indonesia menjadikan Program Jogo Tonggo dapat mudah dikenalkan dan diterapkan di masyarakat (Probosiwi & Putri, 2021).…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Sebagai bangsa yang majemuk, masyarakat Indonesia sudah terbiasa untuk hidup berdampingan dengan segala keragaman budaya yang ada sebagai wadah interaksi sosial dengan menjunjung nilai dan kebersamaan. Kentalnya budaya gotong royong di Indonesia menjadikan Program Jogo Tonggo dapat mudah dikenalkan dan diterapkan di masyarakat (Probosiwi & Putri, 2021).…”
Section: Pembahasanunclassified
“…Program Jogo Tonggo merupakan implementtasi nilai solidaritas sosial masyarakat khususnya gotong royong sebagai modal, spirit, dan alat yang dimanfaatkan untuk melawan COVID-19 (Probosiwi & Putri, 2021). Program Jogo Tonggo yang dicetuskan Pemerintah Jawa Tengah ini menjadi tulang punggung dalam strategi pencegahan dan pengendalian COVID-19.…”
Section: Gambar 3 Pelaksanaan Evaluasi Kegiatanunclassified
“…Recent study also found that social capital in one of the villages in Purworejo Regency, Central Java Province was very helpful in overcoming the socio-economic impact of COVID-19, including through the jogo-tonggo (taking care of neighbors) program, namely aiding with raw or cooked food. to those who have been severely affected by the economy from the COVID-19 pandemic and those who are self-isolating (Probosiwi & Putri, 2021)data were collected by in-depth interviews with respondents who were selected by snowball sampling. The research was conducted in Purworejo Regency.…”
Section: Poverty In Indonesia During Covid-19 Pandemicmentioning
confidence: 99%
“…(2020), Maslina dkk. (2020), Gunawan (2020), Widisuseno (2020), Probosiwi (2021), serta Hekmatyar dan Vonika (2021). Hal ini memperlihatkan bahwa gagasan tentang pemberian bantuan bahan pangan pada warga masyarakat yang kekurangan secara ekonomi bersifat universal dan sangat relevan dilakukan dalam situasi pandemi ini.…”
Section: Pendahuluanunclassified